Bariatric surgery in patients with obesity and end-stage renal disease - Khajeh, Elias; Aminizadeh, Ehsan; Dooghaie Moghadam, Arash; Sabetkish, Nastaran; Abbasi Dezfouli, Sepehr; Morath, Christian; Zeier, Martin; Nickel, Felix; Billeter, Adrian; Müller, Beat P.; Mehrabi, Arianeb (Surgery for obesity and related diseases, 2023)
Background - Bariatric surgery has been suggested as a treatment for obesity and end-stage renal disease (ESRD). Although the number of bariatric surgeries in patients with ESRD is increasing, its safety and effectiveness in these patients are still controversial and the surgical method of choice in these patients is under debate. - Objectives - To compare the outcomes of bariatric surgery between patients with and without ESRD and to assess different methods of bariatric surgery in patients with ESRD. - Setting - Meta-analysis. - Methods - A comprehensive search was conducted in Web of Science and Medline (via Pubmed) until May 2022. Tow meta-analyses were performed: A) to compare bariatric surgery outcomes among patients with and without ESRD, and B) to compare outcomes of Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) in patients with ESRD. Using a random-effect model, odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals (CIs) were computed for surgical and weight loss outcomes. - Results - Of 5895 articles, 6 studies were included in meta-analysis A and 8 studies in meta-analysis B. The risk of bias was moderate to serious among studies. Major postoperative complications (OR = 2.82; 95% CI = 1.66-4.77; P = .0001), reoperation (OR = 2.66; 95% CI = 1.99-3.56; P < .00001), readmission (OR = 2.37; 95% CI = 1.55-3.64; P < .0001), and in-hospital/90-d mortality (OR = 4.03; 95% CI = 1.80-9.03; P = .0007) were higher in patients with ESRD. Patients with ESRD also had a longer hospital stay (MD = 1.23; 95% CI = .32-2.14; P = .008). Bleeding, leakage, and total weight loss were comparable among groups. SG showed a 10% lower rate of overall complications and significantly shorter hospital stay than RYGB did. The quality of evidence was very low for the outcomes - Conclusions - Bariatric surgery in patients with ESRD seems to have higher rates of major complications and perioperative mortality than in patients without ESRD, but a comparable rate of overall complications. SG has fewer postoperative complications and could be the method of choice in these patients. These findings should be interpreted cautiously in light of the moderate to high risk of bias in most included studies.